Temporal elevation of blood pressure is associated with increased risk of sudden cardiac arrest - Yun Gi Kim; Kyongjin Min; Joo Hee Jeong; Seung-Young Roh; Kyung-Do Han; Jaemin Shim; Jong-Il Choi; Young-Hoon Kim (Scientific Reports, 2024)
Abstract Hypertension is a known risk factor for sudden cardiac arrest (SCA). However, the role of temporal changes in blood pressure on the risk of SCA is not fully understood. This study was conducted to determine whether a temporal increase or decrease in blood pressure is associated with the risk of SCA. This study was based on nationwide healthcare insurance data. Individuals who underwent nationwide health check-ups in 2009 and 2011 were analyzed. A total of 2,801,153 individuals were evaluated for 8100 SCA events during the 17, 740, 420 person-years of follow-up. In a multivariate analysis, there were linear association between the degree of temporal elevation of systolic blood pressure (SBP) and the risk of SCA: (i) adjusted-hazard ratio (HR) 1.11 (p = 0.001) in 10 ≤ ΔSBP < 20 (mmHg) group; (ii) adjusted-HR 1.40 (p < 0.001) in 20 ≤ ΔSBP < 40 group; and (iii) adjusted-HR 1.88 (p < 0.001) in 40 ≤ ΔSBP group as compared with the reference group (− 10 ≤ ΔSBP < 10). Temporal increase in diastolic blood pressure (DBP) also a showed significant association with SCA risk with the highest risk observed in ∆DBP ≥ 25 group (adjusted-HR 1.61; p < 0.001) as compared with the reference group (− 5 ≤ ΔDBP < 5). The association between SBP and SCA was not affected by age, sex, presence of diabetes mellitus, or baseline SBP. In conclusion, a temporal increase in blood pressure was significantly associated with the occurrence of SCA, and this association was consistent across all subgroups. However, a temporary decrease in blood pressure does not reduce the risk of SCA. Prevention of elevated blood pressure may play an important role in preventing SCA.